2022
DOI: 10.3389/fneur.2022.765321
|View full text |Cite
|
Sign up to set email alerts
|

Sleep, Pain, and Neurodegeneration: A Mendelian Randomization Study

Abstract: Our aim was to determine whether the genetic liability to sleep and pain-related traits have a causal effect on risk of neurodegeneration in individuals of predominantly European ancestry. We selected five neurodegenerative disorders, namely, age-related macular degeneration (AMD), Alzheimer's disease (AD), amyotrophic lateral sclerosis (ALS), multiple sclerosis (MS), and Parkinson's disease (PD). Sleep duration (SD), short sleep (SS), long sleep (LS), chronotype (CHR), morning person (MP), insomnia (INS), and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 51 publications
(67 reference statements)
0
7
0
Order By: Relevance
“…Following reason can explain why our study found a significant association between sleep duration and AMD but the previous MR study failed. First, the sample size was five-fold increased in this study (150,642) than others (33,976) ( Grover et al, 2022 ). Second, it’s worth noting that the sleep duration only have minimal effect on AMD (OR = 0.983, 95% CI = 0.970–0.996).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Following reason can explain why our study found a significant association between sleep duration and AMD but the previous MR study failed. First, the sample size was five-fold increased in this study (150,642) than others (33,976) ( Grover et al, 2022 ). Second, it’s worth noting that the sleep duration only have minimal effect on AMD (OR = 0.983, 95% CI = 0.970–0.996).…”
Section: Discussionmentioning
confidence: 68%
“…On the contrary, another study failed to detect an association with long sleep in 316 patients with nAMD compared to 500 patients without AMD ( Khurana et al, 2016 ). Besides, a MR study based on the neurodegenerative disorders, including age-related macular degeneration (AMD), Alzheimer’s disease (AD), amyotrophic lateral sclerosis (ALS), multiple sclerosis (MS), and Parkinson’s disease (PD), have not revealed relationships among the sleep duration and AMD (IVW P -value = 0.15) ( Grover et al, 2022 ). In the current study, we found that sleep duration influences the risk of AMD, that is, longer sleep duration reduces the risk of AMD while shorter sleep duration increases the risk of AMD.…”
Section: Discussionmentioning
confidence: 99%
“…These two MR estimates all passed Bonferroni correction (IVW-derived P < 8.33 × 10 –3 , significant). A previous study has used MR approaches to evaluate the effect of SSD and LSD on advanced AMD ( Grover and Sharma, 2022 ) and found no significant effects. The leave-one-out plots ( Supplementary Figure 1 ), the funnel plots ( Supplementary Figure 2 ), the MR-Egger intercept test, Cochran’s Q test, and MR-PRESSO global test ( Table 5 ) all suggested no apparent heterogeneity or pleiotropy in these results.…”
Section: Resultsmentioning
confidence: 99%
“…AMD, a representative disease in geriatric ophthalmology, is a well-known disease with heritable characteristics, which was the initial focus of GWAS research [66][67][68][69][70]. With these genomic data, MR-based causal studies of dyslipidaemia or other risk factors for AMD have been conducted [71][72][73][74][75][76]. In addition, the C-reactive protein is a hallmark lipid in drusen [77].…”
Section: Discussionmentioning
confidence: 99%